2008
DOI: 10.1007/s11096-008-9265-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective assessment of potential interaction between levofloxacin and warfarin

Abstract: The results of this study reaffirm the hypothesis that concomitant administration of levofloxacin and warfarin leads to INR increase; hence close monitoring of INR is advisable when patients are prescribed this combination of drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Smaller retrospective studies have demonstrated increased INR and bleeding risk with levofloxacin use 21, 26 but a systematic review of the effect of ciprofloxacin, levofloxacin, or moxifloxacin among warfarin users reported that findings were inconsistent across studies. 27 In view of this, this association should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller retrospective studies have demonstrated increased INR and bleeding risk with levofloxacin use 21, 26 but a systematic review of the effect of ciprofloxacin, levofloxacin, or moxifloxacin among warfarin users reported that findings were inconsistent across studies. 27 In view of this, this association should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a statistical review of 30 patients who were hospitalized and concurrently taking warfarin and levofloxacin, statistical analysis revealed a significant increase in the INR with a supporting p -value of 0.0001 [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism of action of the interaction remains unknown. Various mechanisms have been proposed to explain the interaction but it has not been clearly elucidated …”
Section: Case Descriptionmentioning
confidence: 99%
“…According to the literature review conducted by Carrol and Carrol on the interaction between warfarin and fluoroquinolones, there is insufficient evidence to recommend complete avoidance of the two drugs in combination. However, all the case reports that associate concomitant use of warfarin and levofloxacin with an increase in INR, and the reported episodes of bleeding during post‐marketing use, cannot be ignored . No data could be identified in the medical literature indicating an interaction between acenocoumarol and levofloxacin.…”
Section: Case Descriptionmentioning
confidence: 99%